The Hippo Signaling Pathway Manipulates Cellular Senescence - Chiharu Miyajima; Mai Nagasaka; Hiromasa Aoki; Kohki Toriuchi; Shogo Yamanaka; Sakura Hashiguchi; Daisuke Morishita; Mineyoshi Aoyama; Hidetoshi Hayashi; Yasumichi Inoue (Cells)
The Hippo pathway, a kinase cascade, coordinates with many intracellular signals and mediates the regulation of the activities of various downstream transcription factors and their coactivators to maintain homeostasis. Therefore, the aberrant activation of the Hippo pathway and its associated molecules imposes significant stress on tissues and cells, leading to cancer, immune disorders, and a number of diseases. Cellular senescence, the mechanism by which cells counteract stress, prevents cells from unnecessary damage and leads to sustained cell cycle arrest. It acts as a powerful defense mechanism against normal organ development and aging-related diseases. On the other hand, the accumulation of senescent cells without their proper removal contributes to the development or worsening of cancer and age-related diseases. A correlation was recently reported between the Hippo pathway and cellular senescence, which preserves tissue homeostasis. This review is the first to describe the close relationship between aging and the Hippo pathway, and provides insights into the mechanisms of aging and the development of age-related diseases. In addition, it describes advanced findings that may lead to the development of tissue regeneration therapies and drugs targeting rejuvenation.